[Rezension von: Sunderland, Williard, 1965-, Regiony Rossiiskoi imperii] - Sablin, Ivan (Slavic review, 2023)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0037677924000585/resource/name/firstPage-pdf-S0037677924000585a.jpg